DNA mismatch repair deficiency in surgically resected lung adenocarcinoma: Microsatellite instability analysis using the Promega panel. (August 2017) - Takamochi, Kazuya; Takahashi, Fumiyuki; Suehara, Yoshiyuki; Sato, Eiichi; Kohsaka, Shinji; Hayashi, Takuo; Kitano, Shigehisa; Uneno, Toshihide; Kojima, Shinya; Takeuchi, Kengo; Mano, Hiroyuki; Suzuki, Kenji
Highlights: MSI was identified in 1 (0.3%) of 341 surgically resected lung adenocarcinomas. Somatic MLH1 gene mutation (p.Glu78*) was identified in the MSI-positive tumor. Mutational signatures associated with smoking and DNA MMR deficiency were observed in the MSI-positive tumor. PD-L1 was not expressed in the MSI-positive tumor. Abstract: Objectives: DNA mismatch repair (MMR) deficiency has recently received increasing attention as a significant biomarker to predict the treatment effect of immune checkpoint inhibitors for various malignant neoplasms. To evaluate MMR status, we analyzed the microsatellite instability (MSI) of lung adenocarcinomas. Materials and methods: Frozen tissues of lung adenocarcinoma and corresponding normal lung were obtained from 341 patients, including 141 with tumors harboring driver gene alterations (50 EGFR gene mutations, 50 KRAS gene mutations, 21 ALK fusions, 10 ROS1 fusions, and 10 RET fusions) and 200 with pan-negative tumors (100 never- or light-smokers and 100 heavy-smokers), who were surgically treated between 2007 and 2015. Genomic DNA extracted from tumors and corresponding normal lung tissues were used for MSI analysis using the Promega panel (5 mononucleotide markers: BAT-25, BAT-26, NR-21, NR-24, and MONO-27 ; and 2 pentanucleotide markers: Penta C and Penta D ). Results: MSI was identified in only 1 pan-negative tumor from a 64-year-old male heavy smoker. MSI was found in 4 mononucleotide markers. Although no clinical background of Lynch syndrome was evident, somatic MLH1 gene mutation was identified. MLH1 was expressed in tumor-infiltrating lymphocytes and was not expressed in cancer cells. PD-L1 was not expressed in cancer cells, and PD-1 was not expressed in tumor-infiltrating lymphocytes. Conclusion: MSI is a rare event in lung adenocarcinoma regardless of smoking status and mutation status of driver oncogenes. Accordingly, MMR deficiency status cannot be used as a biomarker for immune checkpoint inhibitor treatment for lung adenocarcinoma.